2016
DOI: 10.4103/ijmr.ijmr_1873_14
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence & correlates of tobacco use among adolescents in Kerala, India

Abstract: Background & objectives:Most tobacco users who initiate its use during adolescence are likely to continue the use into adulthood and contribute to the 90 per cent of premature deaths among tobacco users. In this context the prevalence, patterns and correlates of tobacco use were studied among adolescent school students in Kerala, India.Methods:Total 7560 students from classes 8, 10 and 12, within the age group of 12-19 yr, across 73 schools in Ernakulam district, Kerala, India, selected by cluster random sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 22 publications
4
27
0
1
Order By: Relevance
“…In India, there has been limited research in this regard. 11,12 GATS-2 data is an opportunity to see the prevalence and trends of tobacco use among youth, a decade after GATS-1 and implementation of the Cigarettes and Other Tobacco Products (Prohibition of Advertisement and Regulation of Trade and Commerce, Production, Supply, and Distribution) Act (COTPA). This study analyses the GATS-2 survey data to estimate the prevalence of tobacco use among youth aged between 15 and 24 years in the country and understand the association of sociodemographic factors with it.…”
Section: Introductionmentioning
confidence: 99%
“…In India, there has been limited research in this regard. 11,12 GATS-2 data is an opportunity to see the prevalence and trends of tobacco use among youth, a decade after GATS-1 and implementation of the Cigarettes and Other Tobacco Products (Prohibition of Advertisement and Regulation of Trade and Commerce, Production, Supply, and Distribution) Act (COTPA). This study analyses the GATS-2 survey data to estimate the prevalence of tobacco use among youth aged between 15 and 24 years in the country and understand the association of sociodemographic factors with it.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies among students across urban India have revealed rates of substance use ranging from 7% to 53% (e.g. Gupta et al, 2013; Jaisoorya et al, 2016; Mahanta et al, 2016). Commonly cited reasons for using included easy availability, stress relief and peer group influence.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are in support with another study from Kerala, India which shows that 68 per cent adolescent among smokers as hazardous user. 29 The higher proportion of users in hazardous use category and current use in adolescence could be owing to highly addictive action of tobacco. 30 The mean age of onset of tobacco use of 14.8 yr in this study is comparable to another study from Kerala which reported an age of onset of around 13 year.…”
Section: Discussionmentioning
confidence: 99%